Assessment Model of Levels for Winter Road Maintenance - Tomas Ratkevičius; Alfredas Laurinavičius (The Baltic Journal of Road and Bridge Engineering, 2017)
The limited funding for the road industry leads to economizing in the planning of road network maintenance, to identifying the appropriate priorities of the activities with the greatest benefit for the society. The level of maintenance is the direct assessment of the road operation and maintenance service provided to the road users; it directly affects the road maintenance and for road users costs the better is road maintenance, the road users incur the fewer expenses and vice versa. Insufficient road maintenance in the winter time causes not only the danger of traffic accidents but also worsens the driving conditions, increases the fuel consumption, vehicle depreciation, transportation becomes more expensive. Many results of studies showed that the current choice of maintenance levels in the winter time taking into account only the road category and traffic volume does not ensure the indicators of the most advanced world countries and road functional purpose. The principle of the minimal expenses for the society should be the main criterion in identifying the optimal levels of winter road maintenance. The experience of Lithuania and foreign countries helped in creating the model of assessment of winter maintenance levels for Lithuanian roads of national significance, which can be applied in the other foreign countries as well. This model could be an effective tool for the selection of the optimal maintenance levels, which would economically substantiate the winter road maintenance strategy, that best corresponds to the needs of the society.